Analisi acustica della cattedrale di Carinola - Gino Iannace (mediaGEO soc. coop., 2018)
The goal of this paper is to analyze the acoustic characteristics of the cathedral of Carinola in order to make it available for both cult and conference and musical performances. Measurements to analyze the acoustic parameters were performed "in situ” with an omnidirectional spherical sound source on the altar and microphones placed in the area where the audience sits. In this way, using a three-dimensional geometric model, designed with architectural acoustics software, the sound field within the church was simulated to evaluate improvements to make it more usable. This procedure has allowed us to assess the acoustic characteristics of the church and to provide for passive acoustic correction.